Functional Role of SIL1 in Neurodevelopment and Learning - Shilian Xu; Jia Zhu; Kai Mi; Yan Shen; Xiaomin Zhang (Neural Plasticity)
Background. Sil1 is the causative gene of Marinesco-Sjӧgren Syndrome (MSS). The mutated Sil1 generates shortened SIL1 protein which will form aggregation and be degraded rapidly. Mental retardation is a major symptom of MSS which suggests a role of SIL1 in the development of the central nervous system, but how SIL1 functions remains unclear. Objectives. The aim of this study is to explore the role of SIL1 in regulating cerebral development and its underlying molecular mechanism. Methods. The basic expression pattern of SIL1 in tissues and cultured cortical neurons is measured by immunostaining and Western blot. The expression of SIL1 is reduced in vitro and in vivo through RNA interference delivered by a lentivirus. The expression of NMDA receptor subunits and the function of the Reelin signaling pathway are then examined by surface biotinylation and Western blot subsequently. Finally, the spatial learning of young mice was assessed by the Barnes maze task. Results. SIL1 deficiency caused a diminished expression of both Reelin receptors and therefore impaired the Reelin signaling pathway. It then inhibited the developmental expression of GluN2A and impaired the spatial learning of 5-week-old mice. Conclusions. These results suggested that SIL1 is required for the development of the central nervous system which is associated with its role in Reelin signaling.